P2Y12 Antagonists in Cardiovascular Disease—Finding the Best Balance Between Preventing Ischemic Events and Causing Bleeding - Fernando, Himawan; McFadyen, James D.; Wang, Xiaowei; Shaw, James; Stub, Dion; Peter, Karlheinz (Frontiers in Cardiovascular Medicine, 2022)
Dual antiplatelet therapy comprising of aspirin and oral P2Y12 receptor antagonists are an established cornerstone of therapy in acute coronary syndromes and percutaneous coronary intervention. As a result, the platelet P2Y12 receptor remains a key therapeutic target in cardiovascular medicine since pharmacological antagonists were first developed in the 1990’s. With a greater understanding of platelet biology and the role played by the P2Y12 receptor in the amplification of platelet activation and thrombus formation, there has been progressive refinement in the development of P2Y12 receptor antagonists with greater potency and consistency of antiplatelet effect. However, challenges remain in the utilization of these agents particularly in balancing the need for greater protection from ischemic events whilst minimizing the bleeding risk and present a real opportunity for the institution of individualized medicine. Future drug developments will provide clinicians with greater avenues to achieve this.